The reversal of the gender gap in education and relative divorce risks: A matter of alternatives in partner choice?. (31st October 2017) - Grow, André; Schnor, Christine; Van Bavel, Jan
Abstract : Recent evidence from the United States suggests that the reversal of the gender gap in education was associated with changes in relative divorce risks: hypogamous marriages, where the wife was more educated than the husband, used to have a higher divorce risk than hypergamous marriages, where the husband was more educated, but this difference has disappeared. One interpretation holds that this may result from cultural change, involving increasing social acceptance of hypogamy. We propose an alternative mechanism that need not presuppose cultural change: the gender-gap reversal in education has changed the availability of alternatives from which highly educated women and men can choose new partners. This may have lowered the likelihood of women leaving husbands with less education and encouraged men to leave less educated spouses. We applied an agent-based model to twelve European national marriage markets to illustrate that this could be sufficient to create a convergence in divorce risks.